Estudo da frequência das neoplasias intra-epiteliais cervicais em mulheres portadoras do vírus da imunodeficiência humana - AZEVEDO, Valéria Nascimento da Gama (Universidade Federal do Pará, 2013)
Cervical cancer and its prescursor lesions are the most important gynecologic manifestations of human immunodeficiency virus infection. Thirty six women infected with human immunodeficiency vírus (HIV) and fifty four uninfected were studied to evaluate the frequency by cervical squamous intraepithelial lesions (SILs), the precursors to invasive cervical cancer. All pacients were interviewed and had a gynecologic examination including Papanicolaou (Pap) test and colposcopy. Biopsies were done on colpocopic abnormalities. The CD4 cell levels were assessed in HIV infected women and we asked about use of antiretrovíral therapy on incidence of SILs, and almost all them used the drugs. The results showed that the frequency of SILs was similar in the two groups. The most of infected women had CD4 levels over than 200 cells/mm3. They were considered immunocompetent. And thirty three women trom thirty six used antiretroviral therapy. In our study the women infected with human immunodeficiency virus, using antiretroviral therapy, with immunocompetent status, had the same frequency of SILs observed on uninfected women.